Diltiazem did not induce gingival overgrowth in rats: a clinical, histological and histometric analysis - Corrêa,Fernanda de Oliveira Bello (2005)
The administration of calcium channel blockers has been associated with gingival overgrowth. However, there are few studies in humans or animals that evaluated the effect of diltiazem on gingival tissues. The present study assessed the influence of diltiazem, at different dosages and treatment duration, on gingival tissues of rats, using clinical, histological and histometric analyses. Eighty young male rats were separated into eight groups according to the dosage and duration of treatment. Rats were treated for 20 or 40 days with a daily subcutaneous injection of 5, 20 or 50 mg/kg of body weight of diltiazem. The results confirmed that diltiazem did not induce gingival overgrowth in rats. For all animals, the evaluation did not show gingival alterations regardless of the dosages and periods of treatment. The histometric analysis showed no significant change in the area of epithelium and connective tissues, although after 40 days of treatment a decrease in the area of connective tissue was observed, without statistically significant difference from control groups. Within the limits of this study, we suggest that diltiazem did not induce gingival overgrowth.